ICRAC controls the rapid androgen response in human primary prostate epithelial cells and is altered in prostate cancer - Holzmann, Christian (Impact Journals LLC, 2013)
Labelled 5α-dihydrotestosterone (DHT) binding experiments have shown that expression levels of (yet unidentified) membrane androgen receptors (mAR) are elevated in prostate cancer and correlate with a negative prognosis. However, activation of these receptors which mediate a rapid androgen response can counteract several cancer hallmark functions such as unlimited proliferation, enhanced migration, adhesion and invasion and the inability to induce apoptosis. Here, we investigate the downstream signaling pathways of mAR and identify rapid DHT induced activation of store-operated Ca(2+) entry (SOCE) in primary cultures of human prostate epithelial cells (hPEC) from non-tumorous tissue. Consequently, down-regulation of Orai1, the main molecular component of Ca(2+) release-activated Ca(2+) (CRAC) channels results in an almost complete loss of DHT induced SOCE. We demonstrate that this DHT induced Ca(2+) influx via Orai1 is important for rapid androgen triggered prostate specific antigen (PSA) release. We furthermore identified alterations of the molecular components of CRAC channels in prostate cancer. Three lines of evidence indicate that prostate cancer cells down-regulate expression of the Orai1 homolog Orai3: First, Orai3 mRNA expression levels are significantly reduced in tumorous tissue when compared to non-tumorous tissue from prostate cancer patients. Second, mRNA expression levels of Orai3 are decreased in prostate cancer cell lines LNCaP and DU145 when compared to hPEC from healthy tissue. Third, the pharmacological profile of CRAC channels in prostate cancer cell lines and hPEC differ and siRNA based knock-down experiments indicate changed Orai3 levels are underlying the altered pharmacological profile. The cancer-specific composition and pharmacology of CRAC channels identifies CRAC channels as putative targets in prostate cancer therapy.